Penyuluhan Hukum dalam Upaya Pencegahan Penyalahgunaan Narkotika di SMP Negri 03 Jrengik Kabupaten Sampang (International Forum of Researchers and Lecturers, 2024)
Narcotics are substances or drugs that can cause decreased consciousness, hallucinations and excitability. In Indonesia itself, drug use is currently critical. Based on survey results from research (BNN), 3.3 million Indonesians are drug addicts, most of whom are young. The lack of knowledge and insight in a nation, especially among teenagers, regarding the impacts caused by drug abuse can worsen the level of drug abuse, plus the development of increasingly sophisticated information technology makes it easier to distribute drugs. Based on the magnitude of the impact caused by drug abuse among teenagers, socialization activities were carried out on the dangers of drug abuse at State Junior High School 3 Jrengik. The aim of carrying out this socialization activity is so that students as targets of the socialization activity can understand the impacts of drug use, both physical, psychological and socio-economic impacts, as well as the criminal sanctions they will face. The research method used is normative law using a statutory approach and a conceptual approach. The results obtained are that law enforcement and the role of schools and local police agencies are very much needed in efforts to prevent narcotics abuse, because if there is no synergy between agencies, it is very possible with access to technology that can make it easier for drug dealers to have a negative influence on students who are still vulnerable. of the influence of promiscuity.